2005
DOI: 10.1063/1.1935132
|View full text |Cite
|
Sign up to set email alerts
|

Size effect on the crystal structure of barium titanate nanoparticles

Abstract: A size effect on crystal structure has been investigated for barium titanate (BaTiO3) nanoparticles of 40-, 140-, and 430-nm sizes, by means of neutron and high-resolution synchrotron x-ray powder-diffraction and Raman-scattering techniques. These samples were prepared by a modified two-step thermal decomposition method from barium titanyl oxalate, resulting in very few lattice impurities. Rietveld analysis of the neutron-diffraction data for the 430-nm- and 140-nm-sized BaTiO3 particles was performed assuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(149 citation statements)
references
References 29 publications
16
125
2
Order By: Relevance
“…Previous studies reported that the c/a ratio of BaTiO 3 particles decreased with particle size. 1),2),20),21), 28) In contrast, this study revealed that the lattice parameters of the inner tetragonal core were almost consistent with that of BaTiO 3 bulk single crystal. The particle size dependence of c/a ratio should be interpreted as the decrease in the volume fraction of inner tetragonal core.…”
Section: Size Effect Of Batio 3 Fine Particlescontrasting
confidence: 43%
“…Previous studies reported that the c/a ratio of BaTiO 3 particles decreased with particle size. 1),2),20),21), 28) In contrast, this study revealed that the lattice parameters of the inner tetragonal core were almost consistent with that of BaTiO 3 bulk single crystal. The particle size dependence of c/a ratio should be interpreted as the decrease in the volume fraction of inner tetragonal core.…”
Section: Size Effect Of Batio 3 Fine Particlescontrasting
confidence: 43%
“…23) Those for 430 nm size BT fine powder prepared from BaTiO(C 2 O 4 )·4H 2 O were a = 3.99900 (8) and c = 4.03265(9) ¡ (c/a = 1.00842) which were determined by high resolution powder neutron diffraction data. 24) The lattice parameters for BT powder obtained by this work were good agreement with those (a = 3.9940(3) and c = 4.0357(5) ¡ (c/a = 1.0104)) for 500 nm size BT powder prepared by hydrothermal reaction. 8) From the chemical analysis no potassium atom was detected and the Ba/Ti ratio in the tetragonal BaTiO 3 was 1.00.…”
Section: Methodssupporting
confidence: 68%
“…4 the endothermic peak in the DTA curve is observed at 130°C for every sample prepared at ²700°C. The T C was somewhat lower than the published value (132°C), 24) and this value agreed well with that for 500 nm size BT powder prepared by hydrothermal reaction. 8) These results suggest that tetragonal BT by this work has similar character to 500 nm size BT powder prepared by hydrothermal reaction.…”
Section: Methodssupporting
confidence: 55%
“…Multilayer ceramic capacitors (MLCC) are indispensable electronic components for advanced electronic technology [2][3][4][5][6][7][8][9][10][11][12] , but larger capacity and smaller size are needed for future electronic devices. To meet these needs, BaTiO 3 particles were downsized, but ferroelectric ceramics lose their ferroelectricity when their particle size is decreased and lose ferroelectricity entirely at a critical size [2][3][4][5][6][7][8][9][10][11] . This is known as the size effect and it impedes the progress of MLCC, so a novel solution has been eagerly anticipated.…”
Section: Morphology Control Of Acicular Batio 3 Particlesmentioning
confidence: 99%